Phenomenon Analysis of the Anomalous AI Tung Tung Sahur Meme - Cindenia Puspasari; Hasan Sazali; Marhamah Marhamah (Electronic Journal of Education, Social Economics and Technology, 2025)
This article analyzes the content of AI meme images, showing how these images construct patterns of thinking through AI meme images. The unit of analysis in this article is the AI meme Tung Tung Sahur, one of many memes featuring a humanoid monster made of wood that resembles a kentongan (traditional Indonesian percussion instrument) that can move and talk. This character is associated with the tradition of waking people up for sahur during Ramadan. Using John Fiske's semiotics, three levels have been identified: at the level of reality, this meme aims to create a comedic and nostalgic effect. However, at the level of representation, it is found to be a signifier indicating the absurdity of thought patterns that can impact younger generations, particularly Generation Alpha, and there is a violation of visual codes that do not align with the sahur tradition during Ramadan. Furthermore, at the ideological level, this meme creates a sense of community among audiences who share similar memories of the sahur tradition. However, it also serves as a small alarm bell indicating a larger underlying issue that significantly influences societal thought patterns and manipulates audiences into consuming the ideology behind the meme.